Cu(I)-catalyzed N,N’-diarylation of natural diamines and polyamines with aryl iodides - Panchenko, Svetlana Petrovna; Averin, Alexei Dmitrievich; Anokhin, Maksim Viktorovich; Maloshitskaya, Olga Aleksandrovna; Beletskaya, Irina Petrovna (Beilstein Journal of Organic Chemistry, 2015)
The Cu(I)-catalyzed N,N’-diarylation of natural diamines and polyamines such as putrescine, cadaverine, spermine, spermidine and their homologues is described. Aryl iodides bearing electron-donating and electron-withdrawing groups have been employed in the study. The CuI/2-(isobutyryl)cyclohexanone/DMF catalytic system has found to be more efficient in the diarylation of diamines and spermine while the CuI/L-proline/EtCN system proved to be preferable for the diarylation of other tri- and tetraamines like spermidine, norspermidine and norspermine.
Keywords: amination; aryl amines; aryl iodides; copper catalysis; polyamines

(untitled) - Pegg, A. E.; Casero, R. A., Jr (Methods Mol. Biol., 2011)

Polyamines in Normal and Neoplastic Growth - Russell, D. H. (Raven Press, 1973)

(untitled) - Casero, R. A.; Marton, L. J. (Nat. Rev. Drug Discovery, 2007)

(untitled) - Huang, Y.; Hager, E. R.; Phillips, D. L.; Dunn, V. R.; Hacker, A.; Frydman, B.; Kink, J. A.; Valasinas, A. L.; Reddy, V. K.; Marton, L. J.; Casero, R. A., Jr; Davidson, N. E. (Clin. Cancer Res., 2003)

(untitled) - Nowotarski, S. L.; Woster, P. M.; Casero, R. A., Jr (Expert Rev. Mol. Med., 2013)

(untitled) - Fraser, A. V.; Woster, P. M.; Wallace, H. M. (Biochem. J., 2002)

(untitled) - Häkkinen, M. R.; Hyvönen, M. T.; Auriola, S.; Casero, R. A., Jr; Vepsäläinen, J.; Khomutov, A. R.; Alhonen, L.; Keinänen, T. A. (Amino Acids, 2009)

(untitled) - Casero, R. A., Jr; Woster, P. M. (J. Med. Chem., 2001)

(untitled) - Díaz, J. E.; Bisceglia, J. Á.; Mollo, M. C.; Orelli, L. R. (Tetrahedron Lett., 2011)

(untitled) - Bisceglia, J. Á.; García, M. B.; Massa, R.; Magri, M. L.; Zani, M.; Gutkind, G. O.; Orelli, L. R. (J. Heterocycl. Chem., 2004)

(untitled) - Haffner, C. D.; Thomson, S. A.; Guo, Y.; Petrov, K.; Larkin, A.; Banker, P.; Schaaf, G.; Dickerson, S.; Gobel, J.; Gillie, D.; Condreay, J. P.; Poole, C.; et al. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Boon, W. R. (J. Chem. Soc., 1947)

(untitled) - Burns, M. R.; LaTurner, S.; Ziemer, J.; McVean, M.; Devens, B.; Carlson, C. L.; Graminski, G. F.; Vanderwerf, S. M.; Weeks, R. S.; Carreon, J. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Heston, W. D. W.; Watanabe, K. A.; Pankiewicz, K. W.; Covey, D. F. (Biochem. Pharmacol., 1987)

(untitled) - Bergeron, R. J.; Weimar, W. R.; Wu, Q.; Feng, Y.; McManis, J. S. (J. Med. Chem., 1996)

(untitled) - da Costa, C. F.; Coimbra, E. S.; Braga, F. G.; dos Reis, R. C. N.; da Silva, A. D.; de Almeida, M. V. (Biomed. Pharmacother., 2009)

(untitled) - Reyes, M. J.; Delgado, F.; Izquierdo, M. L.; Alvarez-Builla, J. (Tetrahedron, 2002)

(untitled) - Hwang, J. Y.; Kim, H.-Y.; Jo, S.; Park, E.; Choi, J.; Kong, S.; Park, D.-S.; Heo, J. M.; Lee, J. S.; Ko, Y.; Choi, I.; Cechetto, J.; et al. (Eur. J. Med. Chem., 2013)

(untitled) - Billman, J. H.; Caswell, L. R. (J. Org. Chem., 1951)

(untitled) - Blank, B.; Michlik, S.; Kempe, R. (Adv. Synth. Catal., 2009)

(untitled) - Wang, L.; He, W.; Wu, K.; He, S.; Sun, C.; Yu, Z. (Tetrahedron Lett., 2011)

(untitled) - Guram, A. S.; Rennels, R. A.; Buchwald, S. L. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Louie, J.; Hartwig, J. F. (Tetrahedron Lett., 1995)

(untitled) - Beletskaya, I. P.; Bessmertnykh, A. G.; Averin, A. D.; Denat, F.; Guilard, R. (Eur. J. Org. Chem., 2005)

Advances in Chemistry Research - Averin, A. D.; Uglov, A. N.; Beletskaya, I. P.; Bessmertnykh, A. G.; Guilard, R. (Pd-catalyzed arylation of polyamines, 2010)

(untitled) - Beletskaya, I. P.; Bessmertnykh, A. G.; Guilard, R. (Tetrahedron Lett., 1997)

(untitled) - Beletskaya, I. P.; Bessmertnykh, A. G.; Guilard, R. (Synlett, 1999)

(untitled) - Yin, H.; Jin, M.; Chen, W.; Chen, C.; Zheng, L.; Wei, P.; Han, S. (Tetrahedron Lett., 2012)

(untitled) - Zhang, C.; Zhan, Z.; Lei, M.; Hu, L. (Tetrahedron, 2014)

(untitled) - Costa, M. V.; Viana, G. M.; de Souza, T. M.; Malta, L. F. B.; Aguiar, L. C. S. (Tetrahedron Lett., 2013)

(untitled) - Anokhin, M. V.; Averin, A. D.; Beletskaya, I. P. (Eur. J. Org. Chem., 2011)

(untitled) - Anokhin, M. V.; Averin, A. D.; Panchenko, S. P.; Maloshitskaya, O. A.; Buryak, A. K.; Beletskaya, I. P. (Helv. Chim. Acta, 2015)

(untitled) - Liu, S.; Rebros, M.; Stephens, G.; Marr, A. C. (Chem. Commun., 2009)

(untitled) - Maruoka, K.; Banno, H.; Nonoshita, K.; Yamamoto, H. (Tetrahedron Lett., 1989)

(untitled) - Ramirez, M. A.; Corona, M. V.; Blanco, M. M.; Perillo, I. A.; Porcal, W.; Salerno, A. (Tetrahedron Lett., 2010)

(untitled) - Chernichenko, N. M.; Averin, A. D.; Buryak, A. K.; Beletskaya, I. P. (Russ. Chem. Bull., 2014)